UGT708S6 from Dendrobium catenatum, catalyzes the formation of flavonoid C-glycosides - Luyao Yu; Kun He; Yu Wu; Kai Hao; Yun Wang; Jinbo Yao; Yuxue Zhao; Qiaoxian Yu; Yanghui Shen; Mengxuan Chen; Ke Xu; Xinfeng Zhang; et al. (BMC Biotechnology)
Abstract Background Dendrobium catenatum is a perennial herb of the genus Dendrobium orchidaceae. It has been known as “Golden Grass, Soft Gold” since ancient times with effects of strengthening the body, benefiting the stomach, generating body fluid, nourishing Yin and clearing internal heat. The flowers of D. catenatum have anti-oxidation, immune regulation and other biological activities. The composition analysis of flowers showed that flavonoid glycosides were significantly accumulated in floral tissue. However, in the flowers of D. catenatum, there was only one case of the UDP-glycosyltransferase (UGT) responsible for the glycosylation of flavonoids has been reported. Result In this study, a new UGT (named UGT708S6) was cloned from D. catenatum flowers rich in O-glycosides and C-glycosides, and its function and biochemical properties were characterized. Through homology comparison and molecular docking, we identified the key amino acid residues affecting the catalytic function of UGT708S6. The glycosyltransferase UGT708S6 was characterized and demonstrated C-glycosyltransferase (CGT) activity in vitro assay using phloretin and 2-hydroxynaringenin as sugar acceptors. The catalytic promiscuity assay revealed that UGT708S6 has a clear sugar donor preference, and displayed O-glycosyltransferase (OGT) activity towards luteolin, naringenin and liquiritigenin. Furthermore, the catalytic characteristics of UGT708S6 were explored, shedding light on the structural basis of substrate promiscuity and the catalytic mechanism involved in the formation of flavonoid C-glycosides. R271 was a key amino acid residue site that sustained the catalytic reaction. The smaller binding pocket resulted in the production of new O-glycosides and the reduction of C-glycosides. This highlighted the importance of the binding pocket in determining whether C-glycosides or O-glycosides were produced. Conclusions The findings suggest that UGT708S6 holds promise as a new glycosyltransferase for synthesizing flavonoid glycosides and offer valuable insights for further understanding the catalytic mechanisms of flavonoid glycosyltransferases.